2010
DOI: 10.1158/1078-0432.ccr-10-0207
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-196 Is Upregulated in Glioblastoma But Not in Anaplastic Astrocytoma and Has Prognostic Significance

Abstract: Purpose: MicroRNAs (miRNA) are short noncoding RNAs that can play critical roles in diverse biological processes. They are implicated in tumorigenesis and function both as tumor suppressors and as oncogenes. The clinical significance of miRNA expression profiles in malignant gliomas remains unclear.Experimental Design: In this study, we examined the expression levels of 365 mature human miRNAs in 12 malignant gliomas, including 8 glioblastomas and 4 anaplastic astrocytomas, using TaqMan realtime quantitative P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 50 publications
8
135
1
3
Order By: Relevance
“…Other papers have demonstrated that miRNAs can be used for tumor classification and grading 66,67 in addition to the diagnosis 23 , prognosis 22,23 and prediction of therapeutic efficacy 69,69 of tumors. The discovery of miRNAs in the serum of cancer patients 70 opened up the exciting possibility of using miRNAs as non-invasive biomarkers.…”
Section: Micrornas As Biomarkers For the Diagnosis And Prognosis Of Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Other papers have demonstrated that miRNAs can be used for tumor classification and grading 66,67 in addition to the diagnosis 23 , prognosis 22,23 and prediction of therapeutic efficacy 69,69 of tumors. The discovery of miRNAs in the serum of cancer patients 70 opened up the exciting possibility of using miRNAs as non-invasive biomarkers.…”
Section: Micrornas As Biomarkers For the Diagnosis And Prognosis Of Gmentioning
confidence: 99%
“…Multivariate analysis showed that the expression of both these miRNAs is a predictor of overall survival in glioblastoma patients 22,23 . Analysis of miRNA expression data in glioblastoma patients (n = 222) derived from the TCGA dataset identified an expression signature of ten miRNAs that can predict glioblastoma (GBM) patient survival 71 .…”
Section: Micrornas As Biomarkers For the Diagnosis And Prognosis Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…The signature included three miRNAs (miR‐20a, miR‐106a, and miR‐17‐5p) that were protective and seven (miR‐31, miR‐222, miR‐148a, miR‐221, miR‐146b, miR‐200b, and miR‐193a) that were risky with respect to the association between their expression and patient survival. Additionally, other studies have found that high expression of miR‐21, miR‐182, and miR‐196 as well as low expression of miR‐181b and miR‐106a are associated with poor patient outcomes 19, 85, 86.…”
Section: Introductionmentioning
confidence: 97%
“…TaqMan miRNA Reverse Transcription kit (Life Technologies™) utilizando-se primers específicos para os miRNAs miRNA-1, miRNA-7, miRNA-10b, miRNA-196a e para o gene de referência RNU48, pequenos RNAs nucleares (Guan et al, 2010 histograma e o conteúdo de DNA distribui as células em "G1+G0", "S" e "G2+M". A discriminação entre as diferentes fases do ciclo é feita pela intensidade de fluorescência, sendo que a fase "G2+M" sempre apresenta o dobro de fluorescência que a fase "G1+G0", pois o DNA nesta fase encontra-se duplicado, enquanto a distância entre "G1+G0" e "G2+M", apresenta uma quantidade intermediária de DNA sendo caracterizada como a fase de síntese, "S".…”
Section: Síntese De Cdna Para Mirnas Específicosunclassified